Unlocking the Potential of Small Businesses: A Key Factor in Driving Business Success - Mohamad Bastomi; Heri Pratikto; Ludi Wishnu Wardana (Cita Konsultindo Research Center, 2024)
Micro and small enterprises (MSMEs) are a category of small and medium-sized enterprises (SMEs) that have contributed to Indonesia's economic development. In this study, we aim to explore the impact of MSMEs in the food and beverage sector in Malang City Indonesia. The sample consists of 93 MSMEs from the Food and Beverage sector in Malang city. The data was analyzed using Structural Equation Model (SEM). The results showed that venture capital, government support, and entrepreneurial mindset have a significant influence on business success. It is important for MSMEs to have proper capital management strategies, including careful financial planning, effective cost control, and regular monitoring of financial performance to ensure that capital is used optimally. In addition, government programs such as financing, skills training, market access, mentorship, and other technical assistance can provide a boost to MSME business growth. On the other hand, the ability to take risks wisely in implementing new ideas is also crucial in driving MSME business success.